Kebutuhan Vitamin pada Ibu Hamil Selama Masa Pandemi Covid-19: Vitamin Necessity of Pregnant Women During The Pandemic Covid-19 - Septi Nur Rachmawati; Ruris Haristiani (MPI Press, 2021)
Introduction: Pregnancy is one of the more important periods in life when increased micronutrients, and macronutrients are most needed by the body; both for the health and well-being of the mother and for the growing foetus and newborn child. During the pandemic of Covid 19, necessity of micronutrients is urgently required to maintain health and immunity system. Objectives: This article aims to describe the necessity of some micronutrients: Vitamin A, vitamin B (B1, B6, B9, B12), vitamin C, vitamin D, vitamin E, and vitamin K especially for pregnant women during pandemic: Vitamin A, vitamin B (B1, B6, B9, B12), vitamin C, vitamin D, vitamin E, and vitamin K. Method: A review of the literature was undertaken using the online databases: BMC, Elsevier, Pubmed, NCBI, Science Direct and Google scholar. Search terms were: vitamin necessity OR vitamin needs OR vitamin required AND pregnant women OR pregnancy OR maternal women AND pandemic OR the pandemic Covid 19 OR during the pandemic Result: from literatures selected, it was found that generally vitamin necessity of pregnant women was higher than adult women. During the pandemic of covid 19, the necessity of vitamins is getting higher. Conclusion: Since pregnant women are vurnerable population during the pandemic covid, it is highly recommended to maintain their health and nutrition by increasing food intake as sources of vitamins.